On the penal system: Code and reforms. (Journal of actual problems of jurisprudence, 2016)
The article provides an analysis of the new Penitentiary Code, the return of the penal system in the Ministry of Interior and the ongoing reforms in the judicial system of the country. The features of the new law. Special attention is paid to the national preventive mechanisms. Formulated by the author’s vision of law situation in the prison system in Kazakhstan.
Keywords: reform; the new Penal Code; the law; and law